2015
DOI: 10.2139/ssrn.2686624
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Distinctiveness in Task Switching: Assessing the Mixture-Distribution Assumption

Abstract: In task switching, increasing the response-cue interval has been shown to reduce the switch cost. This has been attributed to a time-based decay process influencing the activation of memory representations of tasks (task-sets). Recently, an alternative account based on interference rather than decay has been successfully applied to this data (Horoufchin et al., 2011a). In this account, variation of the RCI is thought to influence the temporal distinctiveness (TD) of episodic traces in memory, thus affecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Notably, Horoufchin et al (2011) suggested a loss of repetition benefit in long RCI. The temporal distinctiveness of a task episode might be affected by a random variation of the RCI (Grange, 2016). Hence, the retrieval probability of this episode is influenced.…”
Section: Temporal Dissipation Of Auditory Attention Settingsmentioning
confidence: 99%
“…Notably, Horoufchin et al (2011) suggested a loss of repetition benefit in long RCI. The temporal distinctiveness of a task episode might be affected by a random variation of the RCI (Grange, 2016). Hence, the retrieval probability of this episode is influenced.…”
Section: Temporal Dissipation Of Auditory Attention Settingsmentioning
confidence: 99%